Search for new physics in the dijet mass distribution using 1 fb -1 of pp collision data at √s=7 TeV collected by the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acerbi, E; et al. (2012)
Invariant mass distributions of jet pairs (dijets) produced in LHC proton-proton collisions at a centre-of-mass energy s=7 TeV have been studied using a data set corresponding to an integrated luminosity of 1.0 fb -1 recorded in 2011 by ATLAS. Dijet masses up to ~4 TeV are observed in the data, and no evidence of resonance production over background is found. Limits are set at 95% C.L. for several new physics hypotheses: excited quarks are excluded for masses below 299 TeV, axigluons are excluded for masses below 3.32 TeV, and colour octet scalar resonances are excluded for masses below 1.92 TeV. © 2012 CERN.